Employee Retention and Engagement During Pandemic Period - Fernandes, Winifred (Digital Repository of Theses, 2026)
Background This research holds significance as it examines the critical challenge of maintaining employee engagement and retention within remote work environments during crisis situations, particularly during the COVID-19 pandemic. The sudden transition to remote work disrupted traditional workplace structures and created unprecedented challenges for organizations in sustaining employee motivation, commitment, and performance. Understanding how engagement strategies influence employee satisfaction and loyalty is essential for reducing turnover, maintaining productivity, and supporting long-term organizational stability. As organizations continue to adapt to evolving work models, this research provides valuable insights for leaders and HR professionals to design and implement policies that promote employee well-being, foster collaboration, and cultivate a strong sense of belonging, thereby enhancing both individual and organizational resilience in the post-pandemic era. The primary objectives of this study are to investigate the strategies employed by organizations to sustain employee engagement and retention during the COVID-19 pandemic; to analyze the effectiveness of online engagement initiatives in maintaining employee motivation, satisfaction, and commitment in remote work environments; to identify the key challenges encountered by employees and managers in preserving engagement and alignment with organizational goals during remote work; to examine the influence of recognition, support, and professional development on enhancing employee engagement and retention; and to formulate evidence-based recommendations for developing sustainable engagement strategies that strengthen organizational resilience and retention in future crises and remote work contexts. The research questions guiding this study seek to explore the strategies organizations adopted to sustain employee engagement and retention during the COVID-19 pandemic; assess the effectiveness of online engagement activities in maintaining employee motivation, satisfaction, and commitment in remote work settings; examine the challenges encountered by junior and middle-level managers in keeping employees engaged and aligned with organizational goals while working remotely; evaluate the extent to which recognition, professional development opportunities, and resource allocation influence employee engagement and retention; and identify sustainable practices that organizations can implement to strengthen engagement and retention in future crises or remote work environments. Methodology This research adopts a mixed-method approach, integrating both quantitative and qualitative techniques to develop a comprehensive understanding of employee engagement and retention strategies during the COVID-19 pandemic. Quantitative data were collected through a survey questionnaire administered to employees in the IT sector capturing key variables such as engagement levels, motivation, satisfaction, and commitment in remote work settings. Along with this, semi-structured interviews with managers and HR professionals were conducted to obtain qualitative insights into organizational practices, challenges, and the effectiveness of various engagement strategies. The quantitative data were analyzed using descriptive statistics, while the qualitative data were examined through thematic analysis. This combined approach allowed the study to identify measurable trends alongside deeper contextual perspectives, thereby ensuring a holistic and robust examination of the research objectives. It investigates key factors influencing engagement, including the resources and digital tools required for effective remote work, approaches to maintaining organizational culture and core values, managerial strategies for driving team performance and providing feedback, and methods for employees to stay aligned with organizational goals while celebrating achievements. By exploring how tailored engagement initiatives create a supportive and connected environment, this research highlights strategies that enable employees to remain committed despite physical separation from the traditional workplace, particularly in a technology-driven sector characterized by dynamic and fast-paced work environments. Results The findings reveal that while organizations introduced several online engagement initiatives such as virtual meetings, interactive sessions, online recognition programs, and remote team-building activities. These efforts had limited impact on replicating the engagement levels of physical workplaces. Employees appreciated flexibility, regular communication, and recognition of their progress, but challenges such as lack of face-to-face interaction, inadequate resources, and blurred work-life boundaries continued to hinder full engagement. The study further indicates that employees who received adequate support, clear communication of expectations, and opportunities for skill development exhibited higher levels of motivation, job satisfaction, and commitment, which in turn strengthened their intentions to remain within the organization. However, engagement remained inconsistent across junior and middle-level managers, largely influenced by access to resources, recognition from leaders, and collaborative practices within teams. This research is important as it explores strategies to sustain employee engagement during remote work, particularly in crisis situations like COVID-19. By examining online engagement activities, managerial practices, and organizational support, the study provides insights into maintaining motivation, satisfaction, and commitment. The findings offer practical guidance for IT organizations and contribute to the academic understanding of engagement, remote work, and crisis management. Conclusion This study investigates how organizations addressed employee engagement and retention during the COVID-19 pandemic, with a particular focus on the strategies adopted to sustain motivation, satisfaction, and commitment among employees working remotely. The study demonstrates that organizations employed a combination of online engagement activities, flexible work practices, and supportive leadership behaviors to enhance employee well-being, encourage collaboration, and ensure continued alignment with organizational goals. Through this analysis, the research provides substantive insights into the effectiveness of engagement and retention strategies during periods of crisis, thereby providing valuable guidance for strengthening workforce management in the future organizational challenges. The study concludes that sustaining employee engagement and retention during crises like COVID-19 requires more than surface-level virtual activities. Organizations must adopt holistic strategies that integrate clear communication, recognition, resource support, and opportunities for professional growth. By fostering trust, flexibility, and a culture of care, organizations can cultivate a resilient, motivated, and committed workforce that is better equipped to adapt to disruptions and contribute to long-term organizational success.